Online in-class vs. out-of-class flipped learning models in English as foreign language writing classes - Sengul, Fatma; Bostanci, Hanife Bensen; Kurt, Mustafa (Frontiers in Psychology, 2022)
Flipped learning models are seen as important elements of English as a foreign language (EFL) writing courses as they advance the EFL learners’ writing skills (Pavanelli, 2018). Significantly, studies examining the efficacy of in-class and out-of-class writing models in flipped classroom settings when teaching online EFL writing courses, are still of focus in the Turkish Cypriot context. This investigation aimed to examine the most efficient flipped learning model among the in-class versus out-of-class writing models for the purpose of helping teachers to advance their EFL students’ writing achievement in an online writing setting. In addition, this study sorted to reveal the EFL students’ perceptions toward learning writing through a in-class and out-of-class flipped learning writing models. A mixed methods research design was applied to achieve the aforementioned aims. Twenty-eight EFL students studying at a private universities’ English Language Teaching department constituted the participants of this study. As the findings pointed out, the EFL students in group A, who wrote their essays in-class outperformed those in group B, who wrote their essays out-of-class. Moreover, it was found that the majority of the participants had more positive perceptions towards the in-class flipped classroom writing model. This study highlights that, better student performances are achieved when students write during the class session online with the support of the teacher when implementing a flipped classroom model to teach EFL writing.